Política externa brasileira: cooperação e desenvolvimento na primeira metade da década de 1990 - Racy, Joaquim Carlos (2007)
This thesis analyses brazilian foreign policy from the first half of the 1990 s starting from the presuposition that Brazil s foreign policy in the course of history has been developing itself according postulates that grants it consistency and that, sustained by State s interests and objectives, consolidate an important tradition to the country in that field of the reality. Once considering international cooperation as an instrument of external action that corresponded to the assimetric or complex interdependence theory, one of the main important elements ins this analysis refers to the verification that brazilian s foreign policy from the first part of the 1990 s decade has been marked by a strong action in this sense, with a whole effort developed with the objective of building a cooperation process that would collaborate to the national growth as major purpose of this policy. Brazilian s foreign policy capacity of adaptation, by means of some peculiar characteristics of elaboration and practice of the external policy in the country, and spite of the different forms of manifestation of the Collor and Itamar Franco governments period brought as consequence an external strategy with results that confers a sense of continuity to this policy and give support to its postulations, in a way that under the aim of cooperation Brazil managed realize development in a complex period of its own and worldwide reality. Reached development, although not having ended the country s necessities and having shown itself limited in the social aspect, has allowed Brazil some significant advance, including in terms of international system protagonism